Assessing the vulnerability of urban areas to the urban heat island phenomenon: Strategies for effective mitigation and sustainable urban planning - Alexandra, Pricilia Chika; Philip, Yonathan (Journal of Placemaking and Streetscape Design, 2025)
Background: Urban Heat Island (UHI) is a phenomenon that causes significant temperature differences between urban areas and surrounding suburban or rural areas. This phenomenon can be found even in medium to small-sized cities and is measured based on the temperature difference between urban and rural areas. Methods: This study employs a systematic literature review to analyze research on urban heat islands and applied mitigation strategies. The review follows a structured process, including selection criteria based on albedo, vegetation area, and anthropogenic factors, to identify and classify relevant case studies. The analysis focuses on three mitigation approaches: reducing urban albedo, increasing vegetation, and reducing anthropogenic heat emissions. Findings: In cities, urban heat islands are influenced by factors such as building density, the nature of roads and building surface materials that store heat, lack of green land, and activities carried out in urban areas. With high activity and population density, urban heat islands can cause temperature increases both locally and globally. The increase in temperature in the microclimate in urban areas triggers an increase in death rates due to heat waves, causes discomfort in human activities, and greatly impacts vulnerable groups. This phenomenon will become increasingly widespread due to urbanization which results in urban sprawl which expands urban areas. Conclusion: Urban vulnerability to urban heat islands requires interdisciplinary studies to analyse and develop effective mitigation. The mitigation carried out aims to reduce the negative impact of the urban heat island phenomenon. Novelty/Originality of this article: Three mitigation solutions that can be implemented are reducing urban albedo because albedo can reflect solar radiation, increasing urban vegetation to reduce heat in the surrounding area, and reducing anthropogenic heat emissions by reducing heat emissions from daily activities.